PEMILIHAN KARIER SISWA BERDASARKAN STEREOTIP GENDER DI SMKN 1 PADANG GELUGUR - Eeng Syaputra; Alfi Rahmi; Linda Yarni; Dodi Pasilaputra (STKIP Subang, 2024)
Career selection that is not in accordance with gender causes a gap in the role of a career that is being undertaken, this is because in choosing a career, men and women do not yet know the direction of their future careers according to gender. The objective to be achieved is to see the picture of career selection of SMKN 1 Padang Gelugur students in terms of Gender Stereotypes. This type of research is Quantitative Descriptive. The population in this study were grade XII students with the Total Sampling data collection technique, namely by taking all populations to be used as samples consisting of 38 male students and 38 female students. Data collection in the study used a questionnaire distributed to 76 students, then the data was analyzed using statistical tests. The data processing techniques used were editing, coding, tabulation/telling, finding the percentage of each research item, categorizing and interpreting. The results of the study provide an overview that overall career selection of male students is in the high category with an average percentage of 69.9% and for the overall career selection overview of female students has a percentage of 75% with a high category. It can be seen that the description of career choices is in accordance with the stereotypes of male and female genjer.